2000
DOI: 10.1128/jvi.74.24.11708-11716.2000
|View full text |Cite
|
Sign up to set email alerts
|

Internal Ribosomal Entry Site-Mediated Translation Initiation in Equine Rhinitis A Virus: Similarities to and Differences from That of Foot-and-Mouth Disease Virus

Abstract: Equine rhinitis A virus (ERAV) has recently been classified as an aphthovirus, a genus otherwise comprised of the different serotypes of Foot-and-mouth disease virus (FMDV). FMDV initiates translation via a type II internal ribosomal entry site (IRES) and utilizes two in-frame AUG codons to produce the leader proteinasesLab and Lb. Here we show that the ERAV 5' nontranslated region also possesses the core structures of a type II IRES. The functional activity of this region was characterized by transfection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…FMDV L pro is expressed as long (Lab) and short (Lb) isoforms that result from alternative usage of either the first or second start codon, respectively, with the sequence between the two AUGs predicted to form a stable hairpin structure crucial to IRES activity (39,66). L pro isoforms have indistinguishable activities and specificities and have been proposed to play a role in virulence that may involve the regulation of host interferon responses (89).…”
Section: Resultsmentioning
confidence: 99%
“…FMDV L pro is expressed as long (Lab) and short (Lb) isoforms that result from alternative usage of either the first or second start codon, respectively, with the sequence between the two AUGs predicted to form a stable hairpin structure crucial to IRES activity (39,66). L pro isoforms have indistinguishable activities and specificities and have been proposed to play a role in virulence that may involve the regulation of host interferon responses (89).…”
Section: Resultsmentioning
confidence: 99%
“…Initiation of translation in eukaryotes is regulated by several factors, including mRNA length, the 5Ј-UTR, secondary structure, and the nucleotide context surrounding AUG start codons (7,11,13,17,32). Eukaryotic mRNAs generally adhere to the first AUG rule-in most cases, the AUG codon nearest the 5Ј end is the sole site of initiation of translation (13).…”
Section: Discussionmentioning
confidence: 99%
“…These elements are cis-acting RNA regulatory sequences endowed with the capacity to govern cap-independent translation initiation in mRNAs that are translated when cap-dependent translation is compromised. Subsequent studies demonstrated that IRES elements drive internal initiation of translation in the RNA of all members of the Picornaviridae family (Bakhshesh et al, 2008;Borman and Jackson, 1992;Brown et al, 1991;Hinton and Crabb, 2001;Hinton et al, 2000;Kaku et al, 2002;Kuhn et al, 1990;Nateri et al, 2000;Sweeney et al, 2012;Willcocks et al, 2011;Yu et al, 2011b). The genome of other RNA viruses also contains IRES elements, as illustrated by hepacivirus, pestivirus, dicistrovirus, retrovirus Tsukiyama-Kohara et al, 1992;Vallejos et al, 2010;Wilson et al, 2000), as well as some RNA viruses infecting plants and protozoa (reviewed in Martinez-Salas et al, 2012).…”
Section: Features Of the Picornavirus Untranslated Regionmentioning
confidence: 99%